Getting psychosocial interventions into mental health nursing practice: a survey of skill use and perceived benefits to service users. (11th September 2013) - Butler, Mary Pat; Begley, Mary; Parahoo, Kader; Finn, Sophia
Abstract Aim To investigate the use of psychosocial interventions by mental health nurses following training and perceived benefits to service users. Background Psychosocial interventions are recommended to support the recovery of persons with enduring mental illness. Despite two decades of postgraduate training in psychosocial interventions internationally, implementation challenges still remain. Design A cross‐sectional exploratory, descriptive survey was employed. Methods A survey was mailed to the total population of nurses (n = 58) working in some health regions in Ireland who completed training in psychosocial interventions between 2005–2010. Data were collected between November 2011–January 2012, yielding a response rate of 64%. Descriptive and correlational statistics were used to analyse the data. Results There were statistically significant increases in the use of psychosocial interventions post training. Cognitive behavioural therapy and family interventions were the least used interventions. Assessment and outcome measures, concordance therapy and relapse prevention were preferential interventions. Perceived outcomes for service users were awareness of relapse indicators, enhanced coping skills and fewer admissions. Case load demands, lack of access to supervision and time constraints prevented implementation. Free text comments indicated a dissonance between generic nursing roles and implementation of structured psychosocial interventions in practice. Conclusions The findings indicate a requirement for nursing leadership to legitimize psychosocial interventions as core nursing work. For service users to experience this type of nursing, we propose the nomination of dedicated psychosocial intervention nurses to multidisciplinary teams. Support through guidelines, clinical supervision and audit by senior nurse managers is critical to implementation.